The Potential Role of Cardiac CT in the Evaluation of Patients With Known or Suspected Cardiomyopathy: From Traditional Indications to Novel Clinical Applications - Conte, Edoardo; Mushtaq, Saima; Muscogiuri, Giuseppe; Formenti, Alberto; Annoni, Andrea; Mancini, Elisabetta; Ricci, Francesca; Melotti, Eleonora; Gigante, Carlo; Lorenza, Zanotto; Guglielmo, Marco; Baggiano, Andrea; et al. (Frontiers in Cardiovascular Medicine, 2021)
After 15 years from its advent in the clinical field, coronary computed tomography (CCTA) is now widely considered as the best first-step test in patients with low-to-moderate pre-test probability of coronary artery disease. Technological innovation was of pivotal importance for the extensive clinical and scientific interest in CCTA. Recently, the advent of last generation wide-coverage CT scans paved the way for new clinical applications of this technique beyond coronary arteries anatomy evaluation. More precisely, both biventricular volume and systolic function quantification and myocardial fibrosis identification appeared to be feasible with last generation CT. In the present review we would focus on potential applications of cardiac computed tomography (CCT), beyond CCTA, for a comprehensive assessment patients with newly diagnosed cardiomyopathy, from technical requirements to novel clinical applications.